2018
DOI: 10.1016/j.ihj.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 in the treatment of heart failure: A systematic review of systematic reviews

Abstract: Evidence suggests that the CoQ10 supplement may be a useful tool for managing patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…The predictor obtained an MCC value of 0.490 using all the features and obtained an MCC of 0.560 using the optimal feature subset. [1][2][3][4][5][6] are the performance evaluation indicators of the predictor: Sen represents the sensitivity; Spe represents the specificity; Pre represents the precision; ACC represents the accuracy; F1 represents the F1-measure; MCC represents the Matthews correlation coefficient (MCC). 7 The bolded parts represent the highest value of the corresponding evaluation indicator.…”
Section: The Feature Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictor obtained an MCC value of 0.490 using all the features and obtained an MCC of 0.560 using the optimal feature subset. [1][2][3][4][5][6] are the performance evaluation indicators of the predictor: Sen represents the sensitivity; Spe represents the specificity; Pre represents the precision; ACC represents the accuracy; F1 represents the F1-measure; MCC represents the Matthews correlation coefficient (MCC). 7 The bolded parts represent the highest value of the corresponding evaluation indicator.…”
Section: The Feature Selection Resultsmentioning
confidence: 99%
“…CoQ10 tends to concentrate in organs with high energy requirements, such as the heart, liver, and kidney. Special interest in CoQ10 has arisen from the fact that it associates with many types of diseases, such as heart disease [4,5], chronic kidney disease [6,7], and cancer [8,9]. However, the pharmacology of CoQ10 is not entirely clear, and further comprehensive studies are required for clarity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it showed antidepressive effects and significantly reduced fatigue and improved ergonomic performance during exercise. 28 Other studies assessing the effect of CoQ 10 in combination with other nutrients, such as NADH, in chronic fatigue syndrome 29 and high-dose micronutrients in patients with chronic heart failure 18 have indicated significant improvement in QOL and other dimensions of health care.…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies on the effectiveness of CoQ 10 on QOL in different diseases have indicated that this supplement can have a beneficial effect on QOL. [16][17][18] However, there have been few studies on breast cancer, 9 and to our knowledge, a trial evaluating the effect of CoQ 10 alone in breast cancer patients has not been done yet. Considering the high prevalence of breast cancer, in addition to its importance and effects on all life dimensions of patients, focusing on QOL as it relates to health and finding solutions to ameliorate QOL of these patients seems necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it stabilizes the calcium-dependent ion channel in the myocardium. Its supplementation in patients with cardiopathies, caused by the coenzyme Q10 deficit, showed a cardioprotective effect [182] or reduced mortality in elderly subjects [183]. However, the designed clinical trials with preserved heart failure patients failed to show the benefits of coenzyme Q supplementation [184] in left ventricle dysfunction.…”
Section: Coenzyme Q10mentioning
confidence: 99%